Bacterial Interference with L-Forms - Boris, Marvin (1969)
During the course of studying the effect of normal nasal flora on the growth of L-forms, a clear zone of inhibition was observed around colonies of many coagulase-negative staphylococci. Subsequent investigation demonstrated that Staphylococcus aureus and some S. albus strains produce a substance which is capable of markedly inhibiting the growth of stable staphylococcal and streptococcal L-forms. This interfering substance is separable from the staphylococcal organism and is diffusible through 1.5% agar, but not through a dialysis membrane. It is heat-stable.